Resultado perinatal en recien nacidos de parto vaginal con circular de cordón en el Hospital Regional Docente de Trujillo. Años 2008-2012 - Varas Arteaga, Miguel Eudoro (2015)
Objective: To compare perinatal results of newborns vaginally delivered with nuchal cord. Material and methods: Reviewed 360 clinical histories of the mothers of the infants with and without circular cord born by vaginal delivery in the Hospital Regional Docente de Trujillo between the years 2008-2012 , which met the inclusion and exclusion criteria. Data were analyzed with Chi square test. We considered p <0.05 to indicate statistical differences. Results: Of 180 newborns of vaginal delivery, with circular cord, 20% (36 newborn infants) showed adverse perinatal outcome (p = 0, 590); 1% presented alterations of the fetal cardiac frequency (p=0,317) and 19 % presented liquid amniotic meconial (p=0,681). In terms of the number of circular cord and the presence of adverse perinatal outcome was found that there is a relation between these two variables (p=0,012) Conclusion: The perinatal outcome in newborn infants of vaginal delivery with nuchal cord is not adverse. However, the largest number of turns is related to greater frequency of adverse perinatal outcomes